2014
DOI: 10.1007/s00244-014-0092-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Superparamagnetic Iron Oxide Nanoparticles on Photosynthesis and Growth of the Aquatic Plant Lemna gibba

Abstract: Toxicity of superparamagnetic iron oxide nanoparticles (SPION) was investigated in Lemna gibba plants exposed for 7 days to Fe3O4 (SPION-1), Co0.2Zn0.8Fe2O4 (SPION-2), or Co0.5Zn0.5Fe2O4 (SPION-3) at 0, 12.5, 25, 50, 100, 200 or 400 µg mL(-1). At < 400 µg mL(-1) of SPION exposure, toxicity was indicated by decrease of chlorophyll content, deterioration of photosystem II (PSII) functions, strong production of reactive oxygen species (ROS), and inhibition of growth rate based on fresh weight (52-59 %) or frond n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(23 citation statements)
references
References 38 publications
3
20
0
Order By: Relevance
“…Exposure to CeO 2 had slightly weaker effects on physiological parameters than TiO 2 , and if the latter scenario is correct, this could be due to the lower relative ROS production rate of CeO 2 compared to TiO 2 . 26 Barhoumi et al 39 saw an inhibition of PSII and a corresponding increase in ROS in VOL. XXX ' NO.…”
Section: Resultsmentioning
confidence: 97%
“…Exposure to CeO 2 had slightly weaker effects on physiological parameters than TiO 2 , and if the latter scenario is correct, this could be due to the lower relative ROS production rate of CeO 2 compared to TiO 2 . 26 Barhoumi et al 39 saw an inhibition of PSII and a corresponding increase in ROS in VOL. XXX ' NO.…”
Section: Resultsmentioning
confidence: 97%
“… 47 Due to phytotoxicity, plant growth may be slow, decrease in plant hormones, change in transcriptional genes profile and decreased photosynthetic rate had been observed. 48 - 50 Yusefi-Tanha et al 51 found that small sized CuO nanoparticles (25 nm diameter) were more phytotoxic than large sized CuO nanoparticles (50 nm and 250 nm) to Soybean. Moreno-Olivas et al 52 reported that nanoparticles interaction with plant cell could lead to change in plant genes expression.…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity of SPION against an aquatic plant Lemna gibba has been investigated [ 153 ]. It was found that chlorophyll contents decreased, photosynthetic activity reduced and growth was hampered.…”
Section: Reviewmentioning
confidence: 99%